2019
DOI: 10.1111/hsc.12861
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family involvement in body donation in Hong Kong: A qualitative study of registered donors and bereaved family members

Abstract: Encouraging the public to donate their bodies after death is crucial for anatomy teaching in medical education. In Hong Kong, success may be affected if family members override the registered donors' wish after death, and thus the role of family in body donation is worth more attention. This study aims to examine how family is involved in the process of body donation. A qualitative study was conducted in Hong Kong. Registered donors and bereaved family members were recruited from a body donation scheme organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In line with similar studies conducted in the ME, the difference in religious and cultural backdrops between the region and the western world is deemed to shape participants' attitudes [ 54 , 65 ]. Of course, end-of-life planning often requires consultation with one's family, hence they have been reported to also sway the decision-making process of the individual [ 80 ]. Conversely, Saha et al.…”
Section: Discussionmentioning
confidence: 99%
“…In line with similar studies conducted in the ME, the difference in religious and cultural backdrops between the region and the western world is deemed to shape participants' attitudes [ 54 , 65 ]. Of course, end-of-life planning often requires consultation with one's family, hence they have been reported to also sway the decision-making process of the individual [ 80 ]. Conversely, Saha et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a taboo still exists about disclosing the truth (diagnosis and prognosis) to patients, for fear that this may harm them (Chan, 2011). Recent studies on body donation in Hong Kong also reveal that registered donors may avoid communicating with family members their decisions to donate their bodies after death F I G U R E 1 Flow chart of the study (Chan et al, 2020a(Chan et al, , 2020b). An ACP group may be a way to enhance older adults' openness and motivate them to discuss EOL issues with their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ACP intervention provided by social workers also aims to help older adults to be more open to EOL discussion and enhances the overall QOL of older adults in EOL care (Peres, 2016). In the Hong Kong Chinese context, family is of particularly great importance in EOL decision (Chan, 2011;Chan et al, 2020aChan et al, , 2020b. Social workers in Hong Kong may thus play…”
Section: Many Of These Acp Interventions Are Either Educational or Basedmentioning
confidence: 99%
“…This gives the surviving relatives the right to accept or override the donation decision of a potential body donor (Gürses et al, 2019). Previous reports showed that donors may not discuss their decisions regarding body donation with their relatives (Chan et al, 2020) and in Turkey, nearly half (43.7%) of registered body donors did not involve their relatives in the donation process. Therefore, the anatomy departments included in this study advised potential donors to discuss their decisions with their relatives and encouraged them to persuade their family members to become legal witnesses during the body donation process in order to secure future donations.…”
Section: Discussionmentioning
confidence: 99%